Physiological mechanisms of exogenous organic acids to alleviate aluminum toxicity in seedlings of mungbean, buckwheat, and rice - Liu, Jianmin (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023. Published by Elsevier Masson SAS.